The English teacher's attitude towards internet personal access device (iPad) in teaching and learning process - Miftahul Jannah (Universitas Syiah Kuala, 2021)
Regardless of the integration of technology into English learning at school brings an abundance of advantages, there are still very few teachers who have been implementing technology. iPad as a learning medium in English language learning has been widely applied in many countries. However, the use of iPad for English language learning in Banda Aceh is still considered uncommon. Descriptive qualitative research with a case study approach was carried to find out an English teacher’s attitude towards the integration of iPad in English teaching-learning class in Al-Azhar Cairo Islamic Junior High School in Banda Aceh. An observation sheet and guided interview were used to gather the data. The data analysis was processed in the form of condensation data, display data, and conclusion data which are proposed by Miles, Huberman, and Saldana (2014). The findings show that the English teacher delivered 91 utterances consisted of 34 affective attitudes, 28 conative attitudes, 16 evaluative attitudes, and 13 cognitive attitudes. The highest frequency attitude showed by the teacher is the affective attitude meanwhile the lowest is the cognitive attitude.